2018
DOI: 10.1111/aos.13901
|View full text |Cite
|
Sign up to set email alerts
|

Rotation asymmetry of the human sclera

Abstract: Human sclera is rotationally asymmetric, and its shape varies considerably between subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 20 publications
5
41
1
Order By: Relevance
“…The findings of the current study confirm the belief that the natural shape of the sclera does not exhibit astigmatism patterns like the cornea, but instead is markedly more complex [13]. The results presented here suggest that the sclera is steeper not only at the temporal side as reported by Consejo [29] but also in two other meridians creating angles of nearly 120° between them (Fig 5C and 5D). When Bandlitz [11] measured the limbal scleral radii of 30 subjects, he found that median scleral radii in superior-nasal were the flattest and along temporal direction was the steepest meridian.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The findings of the current study confirm the belief that the natural shape of the sclera does not exhibit astigmatism patterns like the cornea, but instead is markedly more complex [13]. The results presented here suggest that the sclera is steeper not only at the temporal side as reported by Consejo [29] but also in two other meridians creating angles of nearly 120° between them (Fig 5C and 5D). When Bandlitz [11] measured the limbal scleral radii of 30 subjects, he found that median scleral radii in superior-nasal were the flattest and along temporal direction was the steepest meridian.…”
Section: Discussionsupporting
confidence: 91%
“…In his study, Hall [14] also found that corneal-scleral junctions were the sharpest at the nasal but contradictory he found a progressive significant flattening at temporal, inferior and superior junctions. As the asymmetry evaluation analysis in this study was carried out at all meridians (with 1°intervals) neither at wide sectors as in [29, 30] nor cross-sectional slices as in [15, 45], it provides a detailed overview of the scleral shape up to 3 mm beyond the corneoscleral junction. Comparing the statistical figures of the scleral average raw elevation before and after removing the edge, effect showed an increase in the mean values of raw elevation and a decrease in their standard deviations as a result of removing the effect of artificial lift-off caused by the edges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conjunctival hyperaemia and scleral blanching are unwanted phenomena often associated with scleral lens wear. Impingement compression of the conjunctiva to the point where the blood vessels are closed off is an undesirable outcome that will most likely have an effect on wearing time and comfort . Patients that experience discomfort along with conjunctival hyperaemia after extended hours of daily scleral lens wear might eventually reduce wearing time and even develop scleral lens intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…As scleral lenses become more popular, practitioners gain more interest in assessing the anterior scleral shape . Scleral asymmetry, undesired lens seal‐off, and limbal bearing are some of the main fitting challenges associated with scleral contact lenses .…”
Section: Introductionmentioning
confidence: 99%